The second Hyper-Zagreb index of graph operations - Modabish, Abdelhafid; Alameri, Abdu; Gumaan, Mohammed S.; Alsharafi, Mohammed (Journal of Mathematical and Computational Science, 2021)
A graph can be recognized by numeric number, polynomial or matrix which represent the whole graph. Topological index is a numerical descriptor of a molecule, based on a certain topological feature of the corresponding molecular graph, it is found that there is a strong correlation between the properties of chemical compounds and their molecular structure. Zagreb indices are numeric numbers related to graphs. In this study, the second Hyper-Zagreb index for some special graphs, and graph operations has been computed, that have been applied to compute the second Hyper-Zagreb index for Nano-tube and Nano-torus.